Strategies for preventing ventilator-associated pneumonia in adults in the Middle East and North Africa Region: A systematic review and meta-analysis - Omar Abousaad; Aisha Al-Ajji; Noor Abouazab; Adel Aljoaid; Jithin K. Sreedharan (Annals of Thoracic Medicine)
BACKGROUND: Ventilator-associated pneumonia (VAP) is a common complication in intensive care units (ICUs), particularly in patients undergoing prolonged mechanical ventilation. VAP rates vary significantly across regions, with the Middle East and North Africa (MENA) region experiencing relatively high incidences. This study systematically reviews and analyses the efficacy of various VAP prevention strategies in the adult population of the MENA region. METHODS: A systematic review and meta-analysis were conducted following PRISMA guidelines. Electronic databases (PubMed, Scopus, and CINAHL) were searched for studies from January 2004 to May 2024 that investigated VAP prevention strategies in adult ICU patients in the MENA region. Data extraction and quality assessment were performed by multiple independent reviewers. Meta-analysis was carried out using the DerSimonian and Laird random effect models. RESULTS: A total of 10 randomized clinical trials conducted in Iran and Tunisia were included. The studies evaluated various interventions, including respiratory care programs, oral care protocols, and tracheal suction techniques. Significant reductions in VAP incidence were observed with interventions such as aerosolized colistin and comprehensive oral care (e.g., clove mouthwash). However, certain interventions, such as ondansetron and N-acetylcysteine, did not yield significant benefits. CONCLUSION: This meta-analysis highlights effective VAP prevention strategies in the MENA region, with notable improvements in patient outcomes. These findings can potentially help in developing policies and guidelines to enhance VAP prevention efforts across ICUs in the region. Further research is essential to address existing gaps and refine prevention strategies.